2018
DOI: 10.1186/s11556-018-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical, virtual reality-based, and brain exercise on physical, cognition, and preference in older persons: a randomized controlled trial

Abstract: BackgroundPhysical exercise (PE), virtual reality-based exercise (VRE), and brain exercise (BE) can influence physical and cognitive conditions in older persons. However, it is not known which of the three types of exercises provide the best effects on physical and cognitive status, and which exercise is preferred by older persons. This study compared the effects of PE, VRE, and BE on balance, muscle strength, cognition, and fall concern. In addition, exercise effort perception and contentment in older persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 82 publications
(108 reference statements)
5
123
2
Order By: Relevance
“…Additionally, eight secondary outcome articles were identified (Boa Sorte Silva et al, 2018a; Boa Sorte Silva et al, 2017; Eggenberger et al, 2015b; Fraser et al, 2017; Hagovska and Nagyova, 2017; Hagovska and Olekszyova, 2016; Mavros et al, 2017; Middleton et al, 2018) and included along with other manuscripts from the same study. The authors of seven studies (Barban et al, 2017; Boa Sorte Silva et al, 2018b; Htut et al, 2018; Mavros et al, 2017; McDaniel et al, 2014; Middleton et al, 2018; Ten Brinke et al, 2019) were contacted for data and four (Htut et al, 2018; Mavros et al, 2017; Middleton et al, 2018; Ten Brinke et al, 2019) provided data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, eight secondary outcome articles were identified (Boa Sorte Silva et al, 2018a; Boa Sorte Silva et al, 2017; Eggenberger et al, 2015b; Fraser et al, 2017; Hagovska and Nagyova, 2017; Hagovska and Olekszyova, 2016; Mavros et al, 2017; Middleton et al, 2018) and included along with other manuscripts from the same study. The authors of seven studies (Barban et al, 2017; Boa Sorte Silva et al, 2018b; Htut et al, 2018; Mavros et al, 2017; McDaniel et al, 2014; Middleton et al, 2018; Ten Brinke et al, 2019) were contacted for data and four (Htut et al, 2018; Mavros et al, 2017; Middleton et al, 2018; Ten Brinke et al, 2019) provided data.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies used a simultaneous design (Boa Sorte Silva et al, 2018b; Combourieu Donnezan et al, 2018; Hiyamizu et al, 2012; Kitazawa et al, 2015; Laatar et al, 2018; Leon et al, 2015; Mrakic-Sposta et al, 2018; Nishiguchi et al, 2015; Norouzi et al, 2019; Park et al, 2019; Reigal and Mendo, 2014; Rezola-Pardo et al, 2019; Shimada et al, 2018), such as learning complex stepping patterns, solving cognitive tasks while simultaneously performing strength and balance exercises, or conducting computerized cognitive training during aerobic exercise on bikes. Seventeen studies included exergaming interventions (Adcock et al, 2020; Anderson-Hanley et al, 2018; Bacha et al, 2018; Barcelos et al, 2015; Delbroek et al, 2017; Eggenberger et al, 2016; Gschwind et al, 2015; Htut et al, 2018; Hughes et al, 2014; Karssemeijer et al, 2019; Maillot et al, 2012; Pompeu et al, 2012; Schattin et al, 2016; Schoene et al, 2013; Schoene et al, 2015; Song et al, 2018; Stanmore et al, 2019), examples include videogame dancing, cybercycling exergames, and commercial videogames with cognitively challenging components. One study (Eggenberger et al, 2015a) included an exergaming as well as a simultaneous intervention, while another (Rahe et al, 2015) included two sequential training intervention arms, one of which also included motivational counselling.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review with multilevel meta-analysis of 36 studies reported the association between physical exercise and cognitive function (40). However, there are other studies that reported no or only very mild effect of physical exercise on cognitive function (41,42). Our study demonstrated that the MoCA score of the intervention group improved by 1.7 and 2.1 in the post-intervention and post-operative period, while the score did not change in the control group.…”
Section: Discussionmentioning
confidence: 49%
“…Hwang et al utilized a VR training program on 24 older persons with mild NCD, finding that balance and cognitive test scores were improved relative to controls, though details of the VR training program used are unclear [ 82 ]. Htut et al found that a virtual reality video-game-based exercise, which is less beneficial than standard physical activity in assessments of physical ability but better than controls, can also simultaneously improve cognitive function [ 83 ]. Integration of virtual environments with existing exercise modalities, such as stationary cycling, has been found to be appropriate for younger and older individuals alike, while being rated as enjoyable by users, promoting long-term adherence to the exercise program [ 81 , 84 , 85 ].…”
Section: Applications Of Virtual Reality In Cognitive Disorder Tesmentioning
confidence: 99%
“…Patient performance data on tasks can be easily stored in the cloud for analysis. Furthermore, users of some VR training programs describe them as “fun”, which can encourage adherence to a VR-based cognitive training program [ 82 ], and VR exercise programs are more well received than standard physical activity regimens [ 83 ]. As noted previously, virtual reality exercise allows for the easy integration of a cognitive component into the exercise [ 92 ], which can provide tandem physical and cognitive benefits that perhaps take advantage of the promotion of neuroplastic processes induced by exercise [ 92 , 93 ].…”
Section: Applications Of Virtual Reality In Cognitive Disorder Tesmentioning
confidence: 99%